Evaluation of sources, distribution and human bio-accessibility burden of heavy metals pollution in surface sediment and catfish Arius maculatus Thunberg (1792) from Langat and Bernam Rivers, Malaysia - Kadhum, Safaa Abd Alzahra (2017)
The present study was conducted to identify the spatial distribution and sources concentrations of heavy metal from eighteen surface sediment samples of Langat and Bernam rivers using multivariate techniques and pollution indices with their geochemical partitioning in different solid phases and to investigate factors influencing these partitioning on bioaccessibility of metals contamination from geochemical perspectives. The in vitro digestion model in fish tissue are dependent on pH and solid-liquid factors.